Kelelawar Sebagai Ide Dalam Penciptaan Karya Seni Lukis Surealis - Alan Fran Satriyo (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
The aim of creating this final work is to visualize self-reflection by using it as an idea in creating a work of surrealist painting. As well as as a means to deepen the concepts and techniques of painting work. The creation of this final work applies a creation method that is carried out in stages. Starting from the preparation stage, elaboration stage, synthesis stage, concept realization stage, and completion stage. Based on the method that has been carried out, ten work titles were obtained, namely: "Transformation and Regeneration", "Like Time, Wings", "Balance", "Explorer", "Adaptation", "Wading Bats", "Peering Behind the Wings”,“Break through”, “Sleep”.